2016
DOI: 10.1002/mbo3.354
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive responses of outer membrane porin balance of Yersinia ruckeri under different incubation temperature, osmolarity, and oxygen availability

Abstract: The capability of Yersinia ruckeri to survive in the aquatic systems reflects its adaptation (most importantly through the alteration of membrane permeability) to the unfavorable environments. The nonspecific porins are a key factor contributing to the permeability. Here we studied the influence of the stimuli, such as temperature, osmolarity, and oxygen availability on regulation of Y. ruckeri porins. Using qRT‐PCR and SDS‐PAGE methods we found that major porins are tightly controlled by temperature. Hyperosm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…It is possible for microorganisms to regulate the OmpF-OmpC ratio, thereby choosing porins with preferable transmembrane channel diameter, electrostatic potential, and the molecular configuration inside the channel. Regulatory cascades can also allow pathogens to take over permeability by the minor porins such as OmpY or OmpK37 (Knopp and Andersson, 2015; Bystritskaya et al, 2016). Various regulatory cascades can be launched in response to changing environmental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible for microorganisms to regulate the OmpF-OmpC ratio, thereby choosing porins with preferable transmembrane channel diameter, electrostatic potential, and the molecular configuration inside the channel. Regulatory cascades can also allow pathogens to take over permeability by the minor porins such as OmpY or OmpK37 (Knopp and Andersson, 2015; Bystritskaya et al, 2016). Various regulatory cascades can be launched in response to changing environmental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of temperature on effect of the photooxidative stress were examined. E. coli produces two outer membrane proteins, OmpC and OmpF, and these porins play very important roles for survival in aquatic environments [4,17]. Many studies have investigated the effects of light or photosensitizer/light on bacterial survival in aquatic environments [18][19][20].…”
Section: Resultsmentioning
confidence: 99%
“…Many pathogenic bacteria can induce an adaptable response to environmental stimuli, primarily by altering gene expression (Bystritskaya et al, 2016). Recent study showed that T2SS promotes not only pathogenic potency, but also environmental survival (von Tils, Blädel, Schmidt, & Heusipp, 2012).…”
Section: Discussionmentioning
confidence: 99%